Kemampuan Berpikir Kritis Mahasiswa Pendidikan Biologi melalui Penyelesaian Masalah Toksikologi Lingkungan - Laili Munawarah (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2017)
In the era of globalization, science and technology that growing rapidly causing information flow becomes faster and limitless. This has a direct impact on many areas of life, including education. The process of education is required to prepare and produce quality human resources in order to process the information properly and correctly, by developing a culture of critical thinking. Critical thinking is a must-have capability of Bachelor Program’s graduates in National Standards of Higher Education. Critical thinking is important to students because they can train themselves to be rational and choose the problem’s best solution faced through the knowledge they have. But in fact the students are often still difficult to decide the right solution when faced with a problem around them. This problem must be addressed immediately, because it can lead to decreased quality of education and quality of human resources itself. One way to track and describe critical thinking ability is through the provision of problems related to Biology learning subjects. One of the subjects in Biology learning that deals with many issues around life is Environmental Toxicology. Environmental Toxicology issues can encourage students to find solutions to the dangers of contaminants and the work that can be done to minimize the impact of the contaminants. Application of problems in Environmental Toxicology subjects are in the form of questions listed on written tasks. Each question on written tasks refers to Paul-Elder's critical thinking component and Polya's problem solving.